Frontier Capitalism: Norwegian Business Ventures in Northwest Russia 1986 – 2014 - Aaland, Kevin Norman (UiT Norges arktiske universitet, 2019)
Since the dissolution of the Soviet Union, and the subsequent introduction of capitalism and market economy in the 1990s, several Norwegian companies have attempted to establish a profitable business in Russia. Many have failed, while a few have managed to thrive. The aim of the research is to explain the inconsistency of Norwegian business presence in Northwest Russia, the reasons why companies leave, and how some companies have succeeded. The study details the history of Norwegian business establishments in Northwest Russia from 1986 to 2014.